Inhibition of 2-Oxoglutarate Dehydrogenase as a Chemical Model of Acute Hypobaric Hypoxia - Graf, Anastasia; Ksenofontov, Alexander; Bunik, Victoria (Frontiers in Medicine, 2021)
Hypoxia or inhibition of 2-oxoglutarate dehydrogenase complex (OGDHC) are known to change cellular amino acid pools. As OGDHC limits the tricarboxylic acid cycle flux supplying NADH for oxidation in the respiratory chain, we hypothesize that OGDHC inhibition may model limited oxygen consumption under acute hypoxia. In this study, changes in the cerebellar metabolism of amino acids after OGDHC inhibition are quantified and compared to the earlier characterized changes after hypoxia. Significant similarity in the actions of a specific OGDHC inhibitor succinyl phosphonate (SP) and hypoxia, including the dependence of such actions on physiological state, are revealed. In the non-pregnant rat cerebella, either SP or hypoxia increase levels of many amino acids, inducing multiple negative correlations of amino acids with OGDHC activity. In pregnancy, the levels of amino acids are not changed by either SP or hypoxia, but interdependencies of amino acids change significantly. Mostly, SP and hypoxia affect the interdependencies of cerebellar amino acids with OGDHC and tryptophan. Overall, the metabolic interdependencies of amino acids are more sensitive indicators of the induced changes, than the levels of free amino acids. The biochemical changes correspond to physiological effects of SP or hypoxia, characterized by ECG and behavioral parameters. Different amplitudes of qualitatively similar biochemical effects of SP or hypoxia manifest in the stressors-specific physiological reactivities. Our findings indicate that the OGDHC inhibition mimics the action of acute hypobaric hypoxia on the cerebellar amino acid metabolism, with physiological effects of the stressors corresponding to the changes in the amino acids metabolic network.